hsa_circ_0007841: A Novel Potential Biomarker and Drug Resistance for Multiple Myeloma - Gao, Meng; Li, Chengyuan; Xiao, Han; Dong, Hang; Jiang, Siyi; Fu, Yunfeng; Gong, Liying (Frontiers in Oncology, 2019)
Purpose:It has been shown that circular RNA (circRNA) is a key regulatory factor in development and progression of human tumors. However, the working mechanism and clinical significance of most circRNAs remain unknown in human cancer, including multiple myeloma (MM), a hematologic malignancy. Patients and methods:In the present study, high-throughput circRNA microarray was combined with bioinformatics to identify differentially expressed circRNAs in MM. The hsa_circ_0007841 expressions were shown in MM tissues of 86 patients and drug-resistant cell lines and pathological features were detected. Further, the relationship between hsa_circ_0007841 expressions in the MM tissues and pathological features of MM patients were discussed. The role of hsa_circ_0007841 as a potential biomarker and therapeutic target was analyzed. Results:Our results indicated that in MM tissues collected from patients, MM cell lines and drug-resistant cell lines, the hsa_circ_0007841 expression was significantly upregulated. A close connection with prognosis was observed. That is, hsa_circ_0007841 upregulation was correlated with chromosomal aberrations, such as gain 1q21, t(4:14) and mutations in ATR and IRF4 genes. This finding was further verified in large samples. Finally, bioinformatics analysis indicated interaction that 8 differentially expressed miRNAs and 10 candidate mRNAs interacted with hsa_circ_0007841. These results sheds new light on the basic functional research in the future. Conclusion:It was reported for the first time that hsa_circ_0007841 was significantly upregulated in MM. Our study indicated that hsa_circ_0007841 may be a novel biomarker for MM and involved in the progression of MM.